A tree-like nanoporous WO3 photoanode with enhanced charge transport efficiency for photoelectrochemical water oxidation1. Issue 24 (28th June 2015) - Shin, Sun; Han, Hyun Soo; Kim, Ju Seong; Park, Ik Jae; Lee, Myeong Hwan; Hong, Kug Sun; Cho, In Sun
<x xml:space="preserve">Abstract</x> A tree-like nanoporous tungsten trioxide (WO3) photoanode that largely improves the photoelectrochemical water-oxidation performance was synthesized by a laser ablation method.